Pengaruh Metode Pembelajaran dan Kemandirian Belajar Terhadap Sikap Siswa Pada Pembelajaran Sejarah di SMA Negeri 3 Karawang - Taupik Taupik (Jurnal Pendidikan Sejarah, 2017)
This research is purpose to find out the influence of instructional method and learningautonomy to student's attitude in Karawang Senior High School 3. This research is quantitative typewhich uses treatment of experiment design method by level 2x2. Both student's attitude and learningautonomy at learning history are used quetionaire instrument. Based on result of research shows that:(1) student' attitude who think pair share learning method is higer than student's attitude whofollows conventional learning method (2) there are interactions between learning method andconventional learnig (3) student's attitude of learning history which uses think pair share learningmethod and high autonomy learning is higer than student's attitude who follows conventionallearning method with high aoutonomy learning (4)student's attitude who follows think pair sharelearning method at learning history is lower than student's attitude who follows conventionallearning method with low autonomy learning.